PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DALAM PENYUSUNAN DAN PENETAPAN PERATURAN DESA - Nor Emelda (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2015)
The Village Consultative Body is a manifestation of democracy at the villagegovernment. Therefore, this study aims to explore and describe how the implementation of fuction of the village consultative body in preparation and determination of village regulation in Muara Laung II village and to know the  factors that influence of the implementation of the village consultative body in preparation and determination of village regulation in Muara Laung II village.             The method used in this studywas descriptive research with the data analyzed in qualitative. Meanwhile, to collect the data was used observation, interview and documentation. The data resources from this study was chair of BPD, member of BPD, secretary of BPD, society and figure of society.             The results of this study was indicated that the role of BPD in the village of Muara laung II is still weak, caused the minimal number of village regulations generated, as evidenced by only one village regulation that has been established like  APBDes is determined by BPD and there were still village regulations Not yet formed, besides BPD still can not be said to accommodate and contribute the aspirations of the society, because there was not of good socialization with the society that resulted in decisions taken not in accordance with the wishes of the society. The main factor was lack of optimization of the implementation of the functions of BPD in Muara Laung II village that was less of involvement and support of community because unable of BPD to motivation and open opportunity of society participation of society. According to the writer was factors that influence the implementation of BPD function was that BPD still not yet understand assignment and its function that must work by BPD. The writer hope BPD in order can deep knowledge about duty and function of village consultative body in order can correct to implementation its function to be good to the future appropriate with instruction of legislation.             Suggestion, the writer suggested necessarily special existence from the local government to the ways of arranging and make village regulation for the village government and BPD in order to be a legal product.